1977
DOI: 10.1177/070674377702200703
|View full text |Cite
|
Sign up to set email alerts
|

Moral Judgment and Moral Conduct in the Psychopath

Abstract: The relationship between moral conduct and moral judgment was investigated by comparing moral reasoning of a psychopathic sample from a maximum security hospital for the criminal offender with a similar inmate, nonpsychopathic sample, and a group of “normals”. Psychopaths obtained significantly higher scores on the Kohlberg scale of moral judgment than either of the other groups, for whom no differences were found. Results suggest the hypothesis that lack of guilt feelings in psychopaths facilitate the achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 14 publications
(8 reference statements)
1
25
0
Order By: Relevance
“…It is also consistent with early work showing that females high in psychopathy provided deviant responses to a moral dilemma questionnaire under free response conditions, but not when the questionnaire obeyed a multiple choice format (Simon et al, 1951). Indeed, at least one study utilizing a free response format found that psychopathic participants achieved higher scores than controls on Kohlberg’s Moral Judgment scale, somewhat reminiscent of Blair’s finding that they rated both moral and conventional acts as wrong (Link et al, 1977). Taken together, we suggest that the current evidence for moral reasoning deficits among psychopathic individuals is not sufficient to justify arguments for reduced responsibility in psychopathic offenders on the basis of not ‘knowing’ right from wrong.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is also consistent with early work showing that females high in psychopathy provided deviant responses to a moral dilemma questionnaire under free response conditions, but not when the questionnaire obeyed a multiple choice format (Simon et al, 1951). Indeed, at least one study utilizing a free response format found that psychopathic participants achieved higher scores than controls on Kohlberg’s Moral Judgment scale, somewhat reminiscent of Blair’s finding that they rated both moral and conventional acts as wrong (Link et al, 1977). Taken together, we suggest that the current evidence for moral reasoning deficits among psychopathic individuals is not sufficient to justify arguments for reduced responsibility in psychopathic offenders on the basis of not ‘knowing’ right from wrong.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…The notion that psychopathic moral reasoning abilities may be effectively normal has some empirical footing (Aharoni et al, 2012; Cima, Tonnaer, & Hauser, 2010; Link, Sherer, & Byrne, 1977; Simon, Holzenberg, & Unger, 1951; for a review, see Borg & Sinnott-Armstrong, 2013). Therefore, deeper scrutiny into the MCT methods is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Kédia et al, 2008;Moll et al, 2007;Shin et al, 2000], here we show that our brain is differentially specialised in terms of neural substrates for situations implicating suffering in others (altruistic guilt), and those violating inner moral rules (deontological guilt). This formulation has clinical implications for abnormal experiences of guilt in relation to certain neurological disorders [Mendez, 2006], antisocial behavior [Link et al, 1977;Pardini et al, 2003], and obsessive (Rachman, 1993;Salkovskis, 1989;Shafran et al, 1996] or depressive symptoms [Gilbert, 1992;O'Connor et al, 1999O'Connor et al, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Core characteristics that are common to all primary psychopaths can be summarized as; (1) Link, Sherer, & Byrne, 1977;Tassy et al, 2013). As the title of one of these studies aptly states, -psychopaths know right from wrong but do not care‖ (Cima et al, 2010).…”
Section: Biobehavioral Pathways To Primary Psychopathymentioning
confidence: 99%